06 - STATEMENT OF MAXIMAL HR AND COMPARISON WITH PREDICTED HR WITH AGE OF RIO DE JANEIRO SURF FEMALE ATHLETES (Fiep Bulletin - online, 2011)
The surfing is a sport that has shown a great professional development in recent decades. Brazil is among the three world powers alongside the U.S. and Australia, but the practice still has a shortage of scientific studies. Therefore, regular exposure to the exercise over time (physical training) promotes a set of morphological and functional adaptations that increase the capacity to respond to the stress of exercise. Thus, after these adjustments, an exercise of the same absolute intensity would cause less acute stress after a period of training. It is noteworthy that the chronic effects of exercise depend fundamentally on a peripheral adaptation, which involves both a better control and distribution of blood flow, such as specific adaptations of skeletal muscle.The heart rate alteration is a function of a series of events: various stresses, thermal variation, rates of metabolism, hormonal changes, and the degree of training (intensity) .Therefore the present study aimed to describe the Maximal HR and compare the results with the predicted HR max provided by age. This descriptive study has a cross section analysis which is characterized by research method in which the study will be conducted with groups of different ages, same sport, but without support for a longer period. The study subjects were 6 players in the Brazilian ranking of professional surfing with mean age of 32 ± 6.10 years ranked among the top 20 in Brazil. All residents in the State of Rio de Janeiro. Were used: treadmill Imbramed ® brand; Polar® monitor S610 model; Sphygmomanometer Tycos ®; Stethoscope, Lythman ®. The test to verify the HR max was the Bruce protocol, and to calculate the predicted HR max was used the Karvonen equation (220-age). It was used the techniques of descriptive statistics, to enable the characterization of the sample according to selected variables: mean, standard deviation, minimum and maximum for the quantitative variables. It can be seen in the results of two athletes who have reached and exceeded the values predicted by the age Equation. This difference may be due to specific movements of the surf, they all do fitness beyond their specific training, but the type of training these two athletes who peaked can count on running exercises. The specificity of movement of running (which is not specific to the surf) probably had facilitated the two athletes reach their maximum output. It is recommended to adapt the maximum test for surfing people.
Keywords: surf; maximal heart rate; predicted heart rate